Molecular analysis and genome discovery - Rapley, Ralph; Harbron, Stuart (Chichester, West Sussex : John Wiley & Sons, 2011)
Molecular Analysis and Genome Discovery, Second Edition is a completely revised and updated new edition of this successful book. The text provides a comprehensive overview of recent developments in the fast moving field of molecular based diagnostics of disease markers. Key concepts and applications are provided alongside practical information on current techniques currently being researched and developed. Each chapter offers an up-to-date analysis of the subject encompassing the very latest technology platforms and is an essential reference for researchers in the field looking for an up-to-date overview of the subject. The book will also be an indispensable resource for those working in the biotechnology and pharmaceutical industries. New for this edition: chapters on Genotyping through Mutation Detection; Differential Gene Expression; Haplotyping and Molecular Profiling.
Front Matter -- Overview of Genotyping / Monica Bayes, Ivo Glynne Gut -- DNA Chip Analysis in Genome Discovery / Ross N Nazar, Jane Robb -- qPCR, Theory, Reliability and Use in Molecular Analysis / Jamie Murphy, Stephen A Bustin -- DNA Analysis in Droplet-Based Microfluidic Devices / Pinar Ozdemir, Yonghao Zhang -- High-Resolution Melt Profiling / Steven F Dobrowolski, Carl T Wittwer -- Massively Parallel Sequencing / Tracy Tucker, Marco Marra, Jan M Friedman -- Aptamers for Analysis: Nucleic Acids Ligands in the Post-Genomic Era / Pedro Nadal, Alessandro Pinto, Marketa Svobodova, Ciara K O'sullivan -- Use of Nanotechnology for Enhancing of Cancer Biomarker Discovery and Analysis: A Molecular Approach / Farid E Ahmed -- Chip-Based Proteomics / Julian Bailes, Andrew Milnthorpe, Sandra Smieszek, Mikhail Soloviev -- Antibody Microarrays in Proteome Profiling / Mohamed Saiel Saeed Alhamdani, Jorg D Hoheisel -- Biomarker Detection and Molecular Profiling by Multiplex Microbead Suspension Array Based Immunoproteomics / V V Krishhan, Imran H Khan, Paul A Luciw -- Mass Spectrometry in Metabolomics / William J Griffiths, Yuqin Wang -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Molecular diagnosis; Genomics; Proteomics; Pharmacogenomics; Polymerase chain reaction; DNA microarrays; Genomics -- methods; Drug Design; Genetic Techniques; Metabolomics -- methods; Proteomics -- methods; DNA microarrays; Genomics; Molecular diagnosis; Pharmacogenomics; Polymerase chain reaction; Proteomics; Electronic books; Electronic resource; Electronic books